Flap-Related Complications Following Temporal Inverted Internal Limiting Membrane Flap for Macular Hole Repair - Gökçen Deniz Gülpınar İkiz; Ece Özdemir Zeydanlı; Şengül Özdek (Türk Oftalmoloji Dergisi)

(untitled)
Here we report three cases of flap-related complications following temporal inverted internal limiting membrane (ILM) flap technique for the repair of macular holes (MH). The first case showed a flap closure pattern in which the MH completely closed at 2 months spontaneously. The second case showed early anatomical and functional improvement provided by an immediate closure of the MH but developed flap contracture and nasally located epiretinal membrane (ERM) at postoperative 18 months. There was no functional deterioration, thus no further intervention was required. In the third case, early postoperative flap dislocation was observed and an additional surgery to reposition the flap was needed. The flap closure pattern observed with inverted ILM flap techniques may represent the ongoing healing process of large MHs and may be related to delayed spontaneous anatomical closure. ILM flap contracture and ERM formation may be a harmless long-term complication. Dislocation of the ILM flap is an unexpected early postoperative complication that may necessitate a second surgery for flap repositioning.